The Effectiveness Of The Village Head’s Role In The Adjudication Committee Of The Complete Systematic Land Registration (PTSL) Program In Padangsidimpuan City - Nur Oloan Oloan; Zulkarnain Hasibuan; Eny Mayasari (Progressive Law Review, 2026)
Land registration through the Complete Systematic Land Registration (PTSL) program is a strategic government initiative aimed at providing legal certainty over land ownership for all Indonesian citizens. As a member of the Adjudication Committee, the village head (Lurah) holds a pivotal role in facilitating data collection, community coordination, and the resolution of land boundary disputes at the grassroots level. This study aims to analyze the effectiveness of the village head's role within the Adjudication Committee in the implementation of the PTSL program in Sitamiang Baru Village, Padangsidimpuan City. This research employs a qualitative approach with descriptive analysis. Data were collected through in-depth interviews, field observation, and documentation involving key informants including village head officials, BPN (National Land Agency) staff, and community members. The findings indicate that the village head has effectively carried out their role as a member of the Adjudication Committee, as evidenced by active participation in data verification, facilitation of community socialization, and mediation of land boundary disputes. Supporting factors include strong coordination between the village head and BPN officers, as well as high community participation. However, minor challenges such as incomplete administrative documents and limited public awareness were also identified. The study concludes that the village head's role is a determining factor in the success of PTSL implementation, and recommends strengthening capacity-building programs for village heads to sustain program effectiveness.